Wyposażenie liturgiczne kościoła klasztornego w Kraśniku w świetle staropolskich akt krakowskich wizytacji biskupich - Bruździński, Andrzej (Archiwa, Biblioteki i Muzea Kościelne, 2017)
The church in Kraśnik, as presented in the visitation records, was well equipped with the necessary paraments to perform the liturgy. It is also noteworthy that all the church regulations were obeyed. From the description of the visitation, it can be concluded that some of the presented elements were more numerous than it was noted, and in other cases, it was only generally stated that there was a sufficient number of some paraments - this style of description was also typical of other visitation reports. The Canons Regular quite early equipped themselves with church's new books and paraments, as the Church's law required; it proves that Canons Regular met the Church's regulations. The vast majority of books and paraments were acquired by local parish priests, who were also superiors of the Canons community. Paraments and other equipment collected in the Kraśnik church and its sacristy in the Old Polish period were often excellent works of artistic craftsmanship, and therefore, in addition to their basic liturgical function, they had also cultural importance. Being most susceptible to destruction, they shared the fate of the church, the parish and the religious order, hence a small number of the old preserved church equipment.